Preparing for the future: Enhancing financial literacy for elementary school students - Hanjar Ikrima Nanda; Kukuh Yudhistiro; Sheila Febriani Putri; Gina Oktavia; Muhammad Ifan Ali Mustofa (Universitas Muhammadiyah Magelang, 2023)
Shopping is a normal behavior for meeting needs. However, when spending activities lead to consumptive behavior, it can have a negative impact on one's financial management. Based on observations, many parents of students at SDI Sutojayan have expressed concerns about their children's consumerist behavior. This community service aims to enhance children's financial literacy, covering financial sources and money management. The program is implemented in several stages, including the creation of educational teaching aids, financial literacy counseling, and evaluation. The program's results indicate an improvement in children's understanding of money appreciation, as they become aware of the money's origins. The use of educational teaching aids has enhanced their comprehension of how to manage money, whether it's for shopping, charitable activities, or saving.